PSIII-29 Effects of late gestational tall fescue forage system on spring-calving beef cow performance, circulating metabolites, and colostrum quality. (5th December 2019) - Stephenson, Emma L; Heller, Meera C; Kenny, Ann L; Meyer, Allison M
Abstract: Multiparous cows [n = 56; 639 ± 73 (SD) kg initial BW; 5.3 ± 0.4 initial BCS; 5.9 ± 3.0 yr of age; February 16, 2016 average calving date] were allocated by BW, BCS, age, and expected calving date to strip-graze endophyte-infected stockpiled tall fescue (STF; n = 4 pastures; 12.5% CP, 59.5% NDF; DM basis) or consume ad libitum endophyte-infected tall fescue hay (n = 4 uncovered drylots; 7.5% CP, 65.3% NDF; DM basis) for the last 75.0 ± 11.9 d of gestation. At 13.5 ± 1.6 d pre-calving, STF cows were moved to drylots and fed tall fescue haylage (12.6% CP, 61.7% NDF; DM basis). Effects of forage system were included in the model with pen as experimental unit. For gestational metabolites, effects of forage system, day, and their interaction were included with day as a repeated measure. Forage system did not affect (P ≥ 0.35) cow BW. Cows fed STF had greater (P ≤ 0.06) BCS than hay-fed cows at d 32 and 62 of study. Forage system did not affect (P ≥ 0.12) gestational plasma glucose or triglycerides. Serum non-esterified fatty acids (NEFA) were greater (P ≤ 0.005) in hay-fed cows at d 32 and 82 of study and less (P = 0.02) at d 62 of study. After study initiation, serum urea N was greater (P ≤ 0.002) in STF-fed cows than hay-fed cows. At colostrum sampling (6.8 ± 0.9 h postpartum), forage system did not affect (P ≥ 0.10) circulating NEFA, glucose, or triglycerides. Cows fed STF had greater (P ≤ 0.002) serum and colostrum urea N than hay-fed cows. Forage system did not affect (P ≥ 0.17) colostrum protein, lactose, triglyceride, or immunoglobulin concentrations. In conclusion, grazing STF improved cow BCS and altered cow metabolic status but did not affect colostrum quality.